2012
DOI: 10.1186/1748-5908-7-28
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering middle managers' role in healthcare innovation implementation

Abstract: BackgroundMiddle managers have received little attention in extant health services research, yet they may have a key role in healthcare innovation implementation. The gap between evidence of effective care and practice may be attributed in part to poor healthcare innovation implementation. Investigating middle managers' role in healthcare innovation implementation may reveal an opportunity for improvement. In this paper, we present a theory of middle managers' role in healthcare innovation implementation to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
298
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(313 citation statements)
references
References 56 publications
14
298
0
1
Order By: Relevance
“…These individuals are suggested to be in a central and potentially vital position for facilitating quality improvement and change initiatives, yet they require authority and resources to proceed. 6,35,36 However, while the senior managers also have a responsibility for the quality of care, they have an important role in facilitating the implementation of CPGs. In this study, the participation of both front line managers and senior managers in the intervention enabled senior managers to support the frontline managers in their implementation efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These individuals are suggested to be in a central and potentially vital position for facilitating quality improvement and change initiatives, yet they require authority and resources to proceed. 6,35,36 However, while the senior managers also have a responsibility for the quality of care, they have an important role in facilitating the implementation of CPGs. In this study, the participation of both front line managers and senior managers in the intervention enabled senior managers to support the frontline managers in their implementation efforts.…”
Section: Discussionmentioning
confidence: 99%
“…2 A recent theory on middle managers' role in implementation suggests that activities considered important in influencing effectiveness involve how managers diffuse and synthesize information about the innovation, mediate between the implementation strategy and day-to-day activities, and promote the innovation. 6 Still, there is limited knowledge on how managers facilitate effective implementation and even less is known about the function and impact of interventions in the development of leadership in front line management regarding the promotion and support of the implementation of CPGs. CPGs provide recommendations for clinical practice, and are established means to inform EBP.…”
Section: Introductionmentioning
confidence: 99%
“…At the organizational level, several articles have [25][26][27][28][29]36,37 Other studies that have used frameworks like the Barriers Scale and Middle Manager's role in innovation implementation have also found support for individual components of the Innovation Implementation Framework, like "presence of a champion" and "support from management." [30][31][32][33][34] At the clinician level, applications of frameworks like Disruptive Innovation theory, Deskilling and Adaptation, and Sense-Making theory, among others, have helped to demonstrate the crucial role of "innovation-values fit" for enabling behavior change and innovation implementation among frontline clinicians. [44][45][46] Also, several retrospective studies have stressed the role of "innovation attributes" as an important contextual variable in understanding implementation success.…”
Section: Key Insights From Retrospective Articles On Innovation Implementioning
confidence: 99%
“…Given their role characteristics, senior managers are well positioned to champion evidence-informed practice by bridging external and internal sources of evidence that are needed to build knowledge-sharing systems, promote innovation in daily practice, and facilitate practitioner access to performance measurement systems. While it might seem self-evident that administrators might be more involved in tasks requiring evidence use than frontline supervisors, research has found that administrators may be barriers to evidence use and EBP implementation (Aarons et al, 2011;Birken et al, 2012). This difference in understanding of the administrative role suggests that the research has not conclusively determined that agency leaders are positive factors in evidence-based organizational reforms.…”
Section: Synthesis and Implicationsmentioning
confidence: 98%
“…Administrators can play a critical role in supporting the use of evidence. At a basic level, the administrative role is critical for authorizing the time and resources needed to invest in research, gathering and deploying resources to support evidence retrieval, and identifying agency research needs for programs and initiatives (Birkin, Lee, & Weiner, 2012;McBeath & Austin, in press (Moynihan, Wright, & Pandey, 2012) found that transformational leaders promote evidence use indirectly by facilitating goal clarity (around performance targets and pathways) and by supporting a performance-focused organizational culture. This basic finding is supported by other studies referenced in the systematic review conducted by Kroll (2014) as well as research on practitioner evidence use in the human service sector (Palinkas et al, 2011).…”
Section: Organizational Factors Promoting Access To Evidencementioning
confidence: 99%